Konterfekty kresowiaków z ołtarzem i katedra̜ szkolna̜ w tle: z dziejów kontaktów kulturalnych polsko-rosyjskich w okresie mie̜dzypowstaniowym - Wołczuk, Janina (Acta Universitatis Wratislaviensis, 2011)
Zsfassung in engl. Sprache u.d.T.: Portraits of the Borderlanders with the altar and the school lectern in the background : from the history of polish-russian cultural relations in the inter-uprising period